2015
DOI: 10.1016/j.molcel.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Jarid2 Methylation via the PRC2 Complex Regulates H3K27me3 Deposition during Cell Differentiation

Abstract: SummaryPolycomb Group (PcG) proteins maintain transcriptional repression throughout development, mostly by regulating chromatin structure. Polycomb Repressive Complex 2 (PRC2), a component of the Polycomb machinery, is responsible for the methylation of histone H3 lysine 27 (H3K27me2/3). Jarid2 was previously identified as a cofactor of PRC2, regulating PRC2 targeting to chromatin and its enzymatic activity. Deletion of Jarid2 leads to impaired orchestration of gene expression during cell lineage commitment. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
303
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(333 citation statements)
references
References 52 publications
28
303
1
1
Order By: Relevance
“…EZH2 mono-méthyle également le récepteur nucléaire et suppresseur de tumeur ROR (retinoic acid-related orphan nuclear receptor a) qui est alors reconnu par un complexe contenant une ubiquitine ligase entraînant sa dégradation [23]. EZH2 peut enfin méthy-ler JARID2 qui peut alors moduler l'activité catalytique de PRC2, créant ainsi une boucle de régulation [24].…”
Section: Nouvelles Fonctions D'ezh2 Indépendantes De Son Activité H3kunclassified
“…EZH2 mono-méthyle également le récepteur nucléaire et suppresseur de tumeur ROR (retinoic acid-related orphan nuclear receptor a) qui est alors reconnu par un complexe contenant une ubiquitine ligase entraînant sa dégradation [23]. EZH2 peut enfin méthy-ler JARID2 qui peut alors moduler l'activité catalytique de PRC2, créant ainsi une boucle de régulation [24].…”
Section: Nouvelles Fonctions D'ezh2 Indépendantes De Son Activité H3kunclassified
“…Questions remain concerning tissue-and cell type-specificity and context-dependency of EED function, however, because despite lower levels of H3K27me3, the Eed KI/+ mice were able to survive as long as the Eed +/+ mice. Interestingly, a recent study reported that H3K27me3 propagation is regulated by the JARID2 protein, a cofactor of PRC2 (28). Future studies are needed to clarify the perplexing and multifaceted in vivo function of PRC2.…”
Section: The I363m Mutation Increases Susceptibility To Leukemia Andmentioning
confidence: 99%
“…The C-terminal half of JARID2 contains the conserved JmjC and JmjN domains, the ARID domain (a potential DNA-binding domain), and a zinc finger, while the N-terminal half contains an allosteric effect domain, a PRC2-binding region and a nucleosome-binding domain [21,[30][31][32] . How JARID2 influences PRC2, in mechanistic terms, is less well defined.…”
Section: Introductionmentioning
confidence: 99%
“…How JARID2 influences PRC2, in mechanistic terms, is less well defined. Methylated JARID2 mimics methylated H3K27me3 to recruit and activate PRC2, and knockdown/loss-of-function experiments revealed a partial mutual dependence on JARID2 and core PRC2 subunits for target binding [21,[30][31][32][33][34][35][36][37][38][39][40] . JARID2 can bind to long noncoding RNAs (lncRNAs), whose presence stimulates JARID2-EZH2 interactions in vitro and JARID2-mediated recruitment of PRC2 to chromatin in vivo [33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation